2013
DOI: 10.1017/s0954579413000047
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability to depression: A moderated mediation model of the roles of child maltreatment, peer victimization, and serotonin transporter linked polymorphic region genetic variation among children from low socioeconomic status backgrounds

Abstract: Child maltreatment, peer victimization, and a polymorphism of the serotonin transporter gene (5-HTTLPR) were examined as predictors of depressive symptomatology. Children (M age = 11.26, SD = 1.65), including 156 maltreated and 145 nonmaltreated children from comparable low socioeconomic backgrounds, provided DNA samples and self-reports of relational peer victimization, overt peer victimization, and depressive symptoms. Path analysis showed that relational and overt victimization mediated the association betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 136 publications
5
34
0
Order By: Relevance
“…Consistent with adult studies (Caspi et al, 2003), Kaufman et al reported a significant association of 5-HTTLPR genotype with increased depressive symptoms in maltreated children compared to maltreated children with other genotypes or non-maltreated children with the same genotype (Kaufman et al, 2004). This result has been replicated in other studies in youth and appears potentiated by factors such as low social supports (Aslund et al, 2009; Banny, Cicchetti, Rogosch, Oshri, & Crick, 2013; Kaufman et al, 2004). Other studies have demonstrated G×E interactions in the development of internalizing disorders involving genetic variants in the serotonergic, dopaminergic, noradrenergic, glutamatergic and GABAergic systems, other monoamine enzymes, cannabinoids, neuroendocrine, pro-survival factors and inflammatory mediators (for review of mechanisms see: (Mandelli & Serretti, 2013; Nugent et al, 2011).…”
Section: Introductionsupporting
confidence: 79%
“…Consistent with adult studies (Caspi et al, 2003), Kaufman et al reported a significant association of 5-HTTLPR genotype with increased depressive symptoms in maltreated children compared to maltreated children with other genotypes or non-maltreated children with the same genotype (Kaufman et al, 2004). This result has been replicated in other studies in youth and appears potentiated by factors such as low social supports (Aslund et al, 2009; Banny, Cicchetti, Rogosch, Oshri, & Crick, 2013; Kaufman et al, 2004). Other studies have demonstrated G×E interactions in the development of internalizing disorders involving genetic variants in the serotonergic, dopaminergic, noradrenergic, glutamatergic and GABAergic systems, other monoamine enzymes, cannabinoids, neuroendocrine, pro-survival factors and inflammatory mediators (for review of mechanisms see: (Mandelli & Serretti, 2013; Nugent et al, 2011).…”
Section: Introductionsupporting
confidence: 79%
“…Benjet et al found that having two 5-HTTLPR short alleles conferred vulnerability to depression in adolescent girls who were relationally victimized. These findings are not entirely consistent with the Banny et al (2013) findings, but different methodology and design may account for the differential effects and highlight the need for future work. Clearly, these studies demonstrate the important advances that may be made when data on both genetic markers and peer context are known.…”
Section: Crucial Future Directions and Recommendationsmentioning
confidence: 59%
“…More specifically, there was evidence of moderated mediation such that genotype moderated the indirect effect of relational and physical victimization on depressive symptomatology in children (Banny et al, 2013). Using indirect effects testing with bootstrapping procedures that are now widely available, they found that children who were victimized and had the long=long variation 512 OSTROV AND KAMPER of the serotonin transporter gene (5-HTTLPR) were at an increased risk relative to children who had a short allele of the same gene (Banny et al, 2013). Benjet, Thompson, and Gotlib (2010) tested similar questions and found that the 5-HTTLPR polymorphism did not predict level of depression symptoms but that the interaction between the polymorphism and relational peer victimization did significantly predict self-reported depressive symptomatology in girls.…”
Section: Crucial Future Directions and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations